2019
DOI: 10.1080/10428194.2018.1519812
|View full text |Cite
|
Sign up to set email alerts
|

R-CHOP without radiation in frontline management of primary mediastinal B-cell lymphoma

Abstract: Prior to the introduction of rituximab, primary mediastinal B-cell lymphoma (PMBCL) had high rates of treatment failure with cyclophosphamide, doxorubicin, vincristine, and prednisone (CHOP), prompting the use of consolidative mediastinal radiation or more intensive chemotherapy regimens. Cure rates improved dramatically with rituximab, but mediastinal radiation was still commonly employed with R-CHOP. We performed a retrospective review of patients treated with R-CHOP alone without radiation for PMBCL. Of 43 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…107 This question was addressed in the recently completed IELSG-37 trial, and results are awaited with interest. [108][109][110] A bulky mass, slow response to systemic therapy, or a residual mass may predict a higher risk of relapse for DLBCL. 85,[111][112][113][114] As with HL, the use of modified ISRT directed to high-risk sites is supported by the ability of systemic therapy to control small-volume disease sites in early PET complete remission.…”
Section: Primary Mediastinal B-cell Lymphoma Key Evidencementioning
confidence: 99%
“…107 This question was addressed in the recently completed IELSG-37 trial, and results are awaited with interest. [108][109][110] A bulky mass, slow response to systemic therapy, or a residual mass may predict a higher risk of relapse for DLBCL. 85,[111][112][113][114] As with HL, the use of modified ISRT directed to high-risk sites is supported by the ability of systemic therapy to control small-volume disease sites in early PET complete remission.…”
Section: Primary Mediastinal B-cell Lymphoma Key Evidencementioning
confidence: 99%
“…It has also been observed that grade I–II cardiac complications in the DA-R-EPOCH group were more frequent. Another study including 53 cases of PMBCL treated with R-CHOP (n = 21) and DA-R-EPOCH (n = 28), indicated there was no difference in the 1-year PFS and OS between the two groups ( 17 , 75 ). In conclusion, treatments for PMBCL have evolved over time.…”
Section: Frontline Treatmentmentioning
confidence: 99%
“…Moreover, PMBCL cases have been found in non-mediastinal areas, which makes the correct diagnosis of PMBCL difficult ( 14 , 15 ). The poor prognostic characteristics of patients treated with R-CHOP include higher International Prognostic Index (IPI) score, advanced stage, advanced age, and multiple extranodal sites ( 16 , 17 ).…”
Section: Clinical Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…A recently closed clinical trial from the New York Medical College is investigating whether the addition of rituximab and liposomal cytarabine to the FAB Group B backbone can safely reduce the cumulative anthracycline dose and number of intrathecal injections for a subset of patients (NCT01859819). 21 Rituximab has been added to chemotherapy for PMBCL as a substitute for mediastinal radiation, 22,23 thus reducing the risk of cardiotoxicity and breast cancer. In a phase II trial of 51 adults with PMBCL, the addition of rituximab to dose-adjusted etoposide/doxorubicin/ cyclophosphamide 1 vincristine/prednisone (DA-EPOCH) increased EFS from 70% 24 to 93%.…”
Section: Current Therapies Combine Monoclonal Antibodies With Chemothmentioning
confidence: 99%